A Confirmatory Factor Analysis of the Decision Making to Use Service of Sub-District Health Promotion (SDHP) Hospital in Nakhon Si Thammarat Province, Thailand - Sangthong, Kittisak; Lerdsakul, Jintana; Nootong, Siriluk; Chotcharat, Putwimon; Usakun, Ornnucha (Humanities, Arts and Social Sciences Studies, 2020)
The objectives of this research were 1) to conduct a confirmatory factor analysis of the decision making to service quality of Sub-District Health Promotion (SDHP) Hospital in Nakhon Si Thammarat Province, Thailand; 2) to validate a decision making to service quality model using empirical data. A sample size of 670 service users of SDHP was selected. The research instrument used was a questionnaire with a five-rating scale and reliability coefficient of 0.95. The model was validated using SPSS program for basic statistics and a confirmatory factor analysis was performed through LISREL program version 8.82. The major findings were as follows; (1) The decision making to service quality of SDHP consisted of five factors. The order of factor loading values was as follows, tangibility (γ1 = 0.99, p < .05) had the highest value, or tangibility affected decision making to service quality of SDHP the most frequently. This was followed by reliability (γ2 = 0.90, p < .05), responsiveness (γ3 = 0.83, p < .05), assurance (γ4 = 0.70, p < .05) and empathy (γ5 = 0.46, p < .05) respectively and (2) The model of decision making to service quality of SDHP was found to agree with empirical data. Chi-square goodness of fit test value was 279.73 with 100 degrees of freedom, GFI = .95, CFI = .96, AGFI = .93, SRMR = .05 and RMSEA = .05.